Effective Study Hours for Students in the Distribution of Subjects at Vocational High School - Suranto, Suranto; Pramitasari, Endang (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The improvement of the learning quality in schools is closely tied to effective time management. Appropriate scheduling of study hours can play a crucial role in achieving optimal learning outcomes for students. This research aims to analyze and understand how effective study hours can influence the distribution of subjects in schools to enhance students' learning outcomes. The study adopts a qualitative approach with a descriptive research design. The research location is conducted at SMKN 6 Surakarta, utilizing data collection techniques including interviews with students and teachers, documentation related to class schedules, and data triangulation techniques to ensure information validity. Data analysis involves interview transcription, categorization, and the identification of emerging patterns. The findings indicate that the effectiveness of study hours significantly impacts the distribution of subjects. Students experiencing effective study hours tend to have a better grasp of the subjects, while suboptimal study hour distributions can hinder achieving the expected learning outcomes. These findings underscore the importance of thorough planning regarding study hour arrangements to enhance learning effectiveness.